(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with theoretical questions of language cliché, as of status and specific character its linguistic units in approach problem’s of object phraseology in Ukrainian and foreign linguistics.